Financing global policies: but for whom? Taking into account countries vulnerability - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
The Summit's focus on financing vulnerable countries or the fight against vulnerability highlights the fact that the allocation of concessional financing between countries must be considered alongside the mobilization of new resources. This note identifies four principles: (i) the countries ultimately receiving this funding must be identified based on criteria rather than categories of countries: the allocation between countries matters as well as the eligibility for this funding; (ii) the vulnerability of countries, if properly defined, is a major criterion for assessing their needs, without being the only criterion for allocation, or even eligibility; (iii) the vulnerability to be taken into account must be multidimensional and not only linked to climate change; (iv) the allocation criteria must be adapted to the goals of the financial instruments, which is illustrated in particular by the case of "climate" financing.
Keywords: 330